Freedom, democracy and accountability a vision for a new Australian constitution - Harris, Bede (Vivid Publ., 2012)
The contents of the federal Constitution are a mystery to most people, yet it is in the Constitution that are found the rules of how our institutions function, and what powers they may exercise over us. In a time of increasing voter dissatisfaction with how government is conducted in Australia, this book explains how our Constitution works, and why it is in need of reform, covering issues such as how our electoral system can be made fairer, why the innate dignity of the person requires that fundamental freedoms be protected by a Bill of Rights, and how politicians can be made more accountable to Parliament. The book also examines issues such as federalism and an Australian republic, before discussing how civics education could be improved so as to produce citizens who are knowledgeable about their Constitution. The book ends with the full text of a proposed new Australian Constitution